2019
DOI: 10.1039/c9fo00940j
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on foaming and emulsifying properties of different beta-lactoglobulin aggregates

Abstract: Different beta-lactoglobulin aggregates have different foaming and emulsifying properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…The complexity and high sensitivity of globular proteins to environmental conditions make it difficult to describe their impact on the mechanisms of foam (de)stabilization [8,9,11,12,14,26]. Moreover, protein aggregation (reversible or irreversible) can have complex (enhancing/inhibiting) influence on interfacial and foaming properties as compared to those of the respective native protein [8,19,[39][40][41][42][43][44]49,55]. The behavior of proteins at interfaces and in corresponding foam films and foams is governed by the interplay of the protein concentration and the solvent conditions (salt type and concentration, pH), and the unique effect of pH is of special interest.…”
Section: Introductionmentioning
confidence: 99%
“…The complexity and high sensitivity of globular proteins to environmental conditions make it difficult to describe their impact on the mechanisms of foam (de)stabilization [8,9,11,12,14,26]. Moreover, protein aggregation (reversible or irreversible) can have complex (enhancing/inhibiting) influence on interfacial and foaming properties as compared to those of the respective native protein [8,19,[39][40][41][42][43][44]49,55]. The behavior of proteins at interfaces and in corresponding foam films and foams is governed by the interplay of the protein concentration and the solvent conditions (salt type and concentration, pH), and the unique effect of pH is of special interest.…”
Section: Introductionmentioning
confidence: 99%
“…Natural globular β-LG of high purity was extracted from raw milk by heating at 40°C for 1 h to remove lipids, precipitating casein at pH 4.6, precipitating α-albumin at pH 3.7, dialyzing against water at 4°C for 72 h, and freeze-drying (Aschaffenburg and Drewry, 1957;Hu et al, 2019). κ-Carrageenan was supplied by FMC BioPolymer (Gelcarin GP-911NF, Philadelphia, PA) and was converted into sodium type using ion exchange resin (Amberlite IR-120, Sigma Chemical Co., St. Louis, MO; Cao et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In previous works, an intramolecular soluble proteinpolysaccharide complex was found to efficiently stabilize emulsions and protect PUFA (Li et al, 2012a(Li et al, , 2013Yao et al, 2016). In a previous study, we systematically compared the air-water and oil-water interfacial properties of NGBLG, BLGF, and BLGNP, and found that their foaming and emulsifying properties were in the order of BLGF > NGBLG > BLGNP (Hu et al, 2019). In this work, we prepared NGBLG, BLGNP, and BLGF and complexed each with the polysaccharide κ-carrageenan (κ-car).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Globular proteins, such as whey, pea or soy proteins, are typically objects of a few nm diameter. Upon heating, they denature and aggregate into a large range of structures, which can be imaged by simple deposition onto freshly cleaved mica and AFM observation in air or in liquid (Demanèche, Chapel, Monrozier, & Quiquampoix, 2009;Farrokhi, Badii, Ehsani, & Hashemi, 2019;Hu et al, 2019;Ikeda & Morris, 2002;Liu & Wang, 2011;Touhami & Dutcher, 2009;Wei, Cheng, & Huang, 2019;Wei & Huang, 2020). In binary mixtures, single aggregated units may even be recognized (Adal et al, 2017).…”
Section: Imaging Structures and Dynamics At Surfacesmentioning
confidence: 99%